2014
DOI: 10.1111/mmi.12867
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Bacillus anthracis virulence regulator AtxA and effects of phosphorylated histidines on multimerization and activity

Abstract: Summary The Bacillus anthracis virulence regulator AtxA controls transcription of the anthrax toxin genes and capsule biosynthesis operon. AtxA activity is elevated during growth in media containing glucose and CO2/bicarbonate, and there is a positive correlation between the CO2/bicarbonate signal, AtxA activity, and homomultimerization. AtxA activity is also affected by phosphorylation at specific histidines. We show that AtxA crystallizes as a dimer. Distinct folds associated with predicted DNA-binding domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 71 publications
(122 reference statements)
5
63
0
Order By: Relevance
“…The current hypothesis is that, while these proteins have the ability to dimerize, it is the ability of the dimers to come together to form higher-order oligomers that enables them to regulate gene expression. Consistent with this are recent findings that Mga and AtxA can be phosphorylated to modulate their activity and that this is due not to modification of DNA binding but rather to modification of the ability of these proteins to form multimers (25,26,34). Our data here are consistent with the hypothesis that multimerization plays an important role in controlling the activity of Mga-like regulators.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The current hypothesis is that, while these proteins have the ability to dimerize, it is the ability of the dimers to come together to form higher-order oligomers that enables them to regulate gene expression. Consistent with this are recent findings that Mga and AtxA can be phosphorylated to modulate their activity and that this is due not to modification of DNA binding but rather to modification of the ability of these proteins to form multimers (25,26,34). Our data here are consistent with the hypothesis that multimerization plays an important role in controlling the activity of Mga-like regulators.…”
Section: Discussionsupporting
confidence: 81%
“…RivR is a member of the Mga-like family of transcriptional regulators, which includes the GAS protein Mga and the B. anthracis protein AtxA. Recently, it was shown that both Mga and AtxA form multimers and that this function is required for activity (22,(24)(25)(26). Therefore, we wished to determine whether RivR also formed multimers and, if so, what degree of multimers were formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To deduce the molecular mechanism of gene regulation by Mga, we first performed modeling studies with I-TASSER (30)(31)(32). Mga is predicted to share a high degree of structural homology with AtxA, a PRD-containing activator from Bacillus anthracis (PDB accession number 4R6I) (10,33,34). The predicted model has a high template modeling (TM) score of 0.62 Ϯ 0.14 (a score of Ͼ0.5 is reliable), suggesting that the model has the correct topology (30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Bacillus anthracis, the causative agent of the zoonotic infectious disease, anthrax, the plasmid-borne atxA gene encodes a transcription factor required for virulence, since it is necessary for the activation of genes for toxin and protective capsule production (5,6). Other Grampositive bacteria possess genes encoding one or more forms of the ArsC (arsenate reductase) family protein, Spx, which is an RNA polymerase (RNAP)-binding protein directing the expression of large regulons that include genes necessary for pathogenesis (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%